Pre-harvest spray of GABA and spermine delays postharvest senescence and alleviates chilling injury of gerbera cut flowers during cold storage - Meisam Mohammadi (Nature Portfolio, 2021)
Abstract Short vase life, capitulum wilting, neck bending, and postharvest chilling injury (CI) are major disorders have negative impact on quality and marketing of gerbera cut flowers. Low storage temperatures prolonging the vase life, but on the other hand leads serious CI which decreases the quality and consumer preferences. Spermine (SPER) and γ-aminobutyric acid (GABA) were identified as anti-aging factors delay the senescence and elevate the chilling tolerance in many species. Greenhouse-grown gerbera cv. ‘Stanza’ sprayed with 2 mM SPER and 1 mM GABA twice (2 T) or thrice (3 T). Cut flowers were stored at 1.5 °C and 8 °C postharvest to study the effects of GABA and SPER on senescence and CI. Vase life, CI and quality of cut flowers were improved by GABA and SPER treatments. No CI was observed in GABA-treated flowers at 1.5 °C; while, flowers sprayed with water showed severe CI. GABA treatments efficiently prolonged the vase life for 6–7 days more than the control (15 days). GABA and SPER increased the fresh weight, solution uptake, protein and proline contents, catalase, peroxidase, and superoxide dismutase activities, while decreased the electrolyte leakage, H2O2, and malondialdehyde contents, polyphenol oxidase, lipoxygenase, and phospholipase D activities. GABA and SPER significantly prolonged the vase life and prevented degradation of proteins and chilling damage and increased capacity of detoxifying and scavenging of H2O2 and reactive oxygen species (ROS), led to alleviate the negative consequences of the senescence and CI.